2019
DOI: 10.1158/1535-7163.mct-18-1146
|View full text |Cite
|
Sign up to set email alerts
|

Anti–B-cell Maturation Antigen Chimeric Antigen Receptor T cell Function against Multiple Myeloma Is Enhanced in the Presence of Lenalidomide

Abstract: Anti-B-cell maturation antigen (BCMA) chimeric antigen receptor (CAR) T cells have shown promising clinical responses in patients with relapsed/refractory multiple myeloma. Lenalidomide, an immunomodulatory drug, potentiates T cell functionality, drives antimyeloma activity, and alters the suppressive microenvironment; these properties may effectively combine with anti-BCMA CAR T cells to enhance function. Using an anti-BCMA CAR T, we demonstrated that lenalidomide enhances CAR T cell function in a concentrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 33 publications
0
47
0
Order By: Relevance
“…IMiDs costimulate immune effector cells (T, NK) and block immunosuppressive BM accessory cells, that is, myeloid suppressor cells, regulatory T (Treg) and regulatory B (Breg) cells, via cell-cell contact and cytokinemediated mechanisms. 4,[36][37][38][39][40][41][42] In recent preclinical studies, IMiDs coupled with CAR T cells had increased anticancer activity compared with CAR T cells alone, [43][44][45] suggesting that the combination of IMiDs with other novel immunotherapeutic modalities may show enhanced antitumor activity. Until now, the combination of IMiDs with BiTE molecule treatment has not been investigated in MM.…”
Section: Introductionmentioning
confidence: 99%
“…IMiDs costimulate immune effector cells (T, NK) and block immunosuppressive BM accessory cells, that is, myeloid suppressor cells, regulatory T (Treg) and regulatory B (Breg) cells, via cell-cell contact and cytokinemediated mechanisms. 4,[36][37][38][39][40][41][42] In recent preclinical studies, IMiDs coupled with CAR T cells had increased anticancer activity compared with CAR T cells alone, [43][44][45] suggesting that the combination of IMiDs with other novel immunotherapeutic modalities may show enhanced antitumor activity. Until now, the combination of IMiDs with BiTE molecule treatment has not been investigated in MM.…”
Section: Introductionmentioning
confidence: 99%
“…Lenalidomide and other immunomodulatory drugs (IMIDs) can also be used to recover T-cell exhaustion. Preclinical data have demonstrated that lenalidomide enhances the anti-tumor activity and persistence of CAR T cells in different NHL and multiple myeloma models ( 141 143 ). Of note, the already mentioned PLATFORM trial also includes an arm in which patients will receive CC-122, a novel IMID, and the phase 1/2 ZUMA-11 trial (NCT03704298) is investigating the safety and efficacy of axi-cel in combination with utomilumab, a monoclonal antibody that binds 4-1BB and stimulates immune cells, in patients with refractory DLBCL.…”
Section: Novel Car T Cell-based Approaches For B-cell Nhl and Cllmentioning
confidence: 99%
“…Recently, considerable work has been done to study how lenalidomide, an immune-modulatory drug, can be used to potentiate CAR T-cells. Indeed several studies have shown that treatment of CAR T-cells with lenalidomide improved CAR T-cell cytokine release and cytotoxicity in vitro , and improved tumor clearance in mouse models of multiple myeloma and lymphoma ( 124 126 ). In another murine model of CRS, Ruella et al.…”
Section: Discussion: Strategies To Befriend the Tme In Car T-cell Thementioning
confidence: 99%